32 A casenote review of parenteral infusions in dying patients; a response to recent media hype. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Burns, Eilidh; Davis, Carol
Abstract : Background: In the aftermath of the Gosport Independent Panel Report (June 2018), the National Audit of Care at End of Life presented an opportunity to examine the use of continuous parenteral infusions for symptom relief in dying patients. Methods: Casenote review of acute hospital in-patients who died in April 2018 recording patient location, diagnosis and hospital palliative care team (HPCT) involvement. For patients who died on an infusion MDT involvement, rationale for starting infusion, duration and drugs used were recorded. Results: 86 casenotes reviewed. 34/86 (40%) patients died on an infusion. 21/60 (33%) dying of non-malignant conditions and 13/26 (50%) dying of cancer were on an infusion. 29/49 (59%) being reviewed by the HPCT and 5/37 (15%) not known to HPCT were prescribed an infusion. 9/14 (64%) patients on an oncology ward and 8/28 (29%) on a care of the elderly (COTE) ward were on infusions. 30/34 (88%) started infusions including an opioid (12 morphine, range 5–30 mg, median 10 mg; 18 oxycodone, range 5–20 mg, median 5 mg). 33/34 (97%) died with an opioid (12 morphine, range 5–30, median 10 mg; 21 oxycodone, range 5–50 mg, median 5 mg). 19/21 (90%) receiving infusional oxycodone were known to HPCT. Other drugs infused: midazolam (21), anti-secretory (18), levomepromazine (10), haloperidol (5), metoclopramide (2). Mean infusion duration 2.2 days (range 0–13). Conclusions: Patients with non-malignant conditions and those on COTE wards were less likely to die on an infusion. Not all patients with cancer, nor all those known to HPCT, died on an infusion, however, patients on an infusion were more likely to be known to HPCT. Average doses of opioids on starting were low and did not substantially increase, which could be related to the short duration of infusions. Poor documentation precluded detailed qualitative analysis.